Pemetrexed sensitizes cisplatin therapy by inducing ferroptosis in NSCLC cells - Wang, Yumin; Zhang, Xin; Cao, Yuwei; Zhang, Ge; Zhu, Yonglin; Li, Yulin; Chen, Jichao (Frontiers in Pharmacology, 2026)
BackgroundCisplatin (DDP) is the first-in-class drug for advanced and non-targetable non-small-cell lung cancer (NSCLC). Platinum-based chemotherapy combined with pemetrexed (PEM) is frequently recommended as the first-line therapeutic regimen for NSCLC. However, the mechanisms of how PEM boosts the antitumor activity of DDP are largely unknown. Emerging evidence indicated that DDP could induce ferroptosis, a new type of regulated cell death (RCD) characterized by iron-dependent toxic build-up of lipid peroxides on cellular membranes. It is tempting to speculate whether PEM increases the sensitivity of NSCLC to DDP through inducing ferroptosis.MethodsIn the present study, we first used RNA-seq and KEGG analysis to examine differentially expressed genes in PEM-challenged NSCLC cells. The effect of PEM on increased DDP-mediated anticancer activity was examined via a cytotoxicity assay and Western blot. PEM-triggered ferroptosis in DDP-treated NSCLC was observed via a lipid peroxidation assay, a labile iron pool assay, and a Western blot in the presence or absence of ferroptosis inhibitors.ResultsIn the present study, we found that the ferroptosis-related pathway was enriched by PEM. PEM significantly enhanced the ability of cisplatin to inhibit cell viability and proliferation in NSCLC cells. The combination of PEM and DDP synergistically induced ferroptosis, as evidenced by the increased reactive oxygen species (ROS), lipid peroxidation, and Fe2+ and decreased SOD. PEM facilitated DDP-mediated upregulated expression of pro-ferroptosis proteins (ACSL4, 12LOX, COX2, DMT1, TFR1, and TF) and downregulated the expression of anti-ferroptosis proteins (SLC7A11, GPX4, FPN1, FTH1, FTL, DHODH, FSP1, and GCH1). However, the effects were reversed by ferroptosis inhibitor ferrostatin-1 or deferoxamine in NSCLC cells.ConclusionIn summary, these results provide in vitro experimental evidence that PEM boosts the antitumor activity and increases the sensitivity of NSCLC cells to DDP by inducing ferroptosis.